Dengue fever: atypical manifestation - Gangasiddaiah, Nataraj; Nanjundaiah, Nagaraj (International Journal of Research in Medical Sciences, 2017)
Dengue fever is affecting millions of population globally. For the past one decade, we have seen several outbreaks and even causing significant mortality of affected population. We witnessed numerous pattern and multisystem presentation of dengue in this period. The CNS manifestation like encephalitis, polyneuropathy (GB like syndrome) and paresthesias were uncommonly reported priorly. Pancreatitis, polyserositis, carditis of varying severity and hepatic failure are the, some of atypical manifestations observed in recent out breaks. So dengue illness can presents with multi system involvement and can account to significant mortality. Here an attempt was done to present varying, uncommon and atypical manifestation of dengue illness.